2007
DOI: 10.4049/jimmunol.179.4.2584
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Factor 4 (CXC Chemokine Ligand 4) Differentially Regulates Respiratory Burst, Survival, and Cytokine Expression of Human Monocytes by Using Distinct Signaling Pathways

Abstract: Platelet factor 4 (PF4; CXCL4) is an abundant platelet α-granule CXC chemokine with unique functions. Although lacking a chemotactic activity, PF4 initiates a signal transduction cascade in human monocytes leading to the induction of a broad spectrum of acute and delayed functions including phagocytosis, respiratory burst, survival, and the secretion of cytokines. Surprisingly, although these monocyte functions are well defined, only very limited information exists on the specific signaling pathways that are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 54 publications
5
65
0
Order By: Relevance
“…By contrast to SKI, DMS pretreatment of unstimulated cells also results in decreased ROS formation, and increased cell death (data not shown). These data indicate that CXCL4-mediated protection from apoptosis is controlled by SphK.In a recent report we have demonstrated that several cytokines and chemokines were induced in CXCL4-treated monocytes [3]. To examine whether cytokine/chemokine expression is also regulated by SphK, monocytes were preincubated in the presence or absence of a constant dosage of SKI (9 mM).…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…By contrast to SKI, DMS pretreatment of unstimulated cells also results in decreased ROS formation, and increased cell death (data not shown). These data indicate that CXCL4-mediated protection from apoptosis is controlled by SphK.In a recent report we have demonstrated that several cytokines and chemokines were induced in CXCL4-treated monocytes [3]. To examine whether cytokine/chemokine expression is also regulated by SphK, monocytes were preincubated in the presence or absence of a constant dosage of SKI (9 mM).…”
mentioning
confidence: 87%
“…In a recent report we have demonstrated that several cytokines and chemokines were induced in CXCL4-treated monocytes [3]. To examine whether cytokine/chemokine expression is also regulated by SphK, monocytes were preincubated in the presence or absence of a constant dosage of SKI (9 mM).…”
Section: Cxcl4 Differentially Regulates Genes Involved In S1p Metabolismmentioning
confidence: 99%
See 3 more Smart Citations